2021
DOI: 10.1186/s40792-021-01130-w
|View full text |Cite
|
Sign up to set email alerts
|

Bowel obstruction due to Chlamydia trachomatis: a case report and review of literature

Abstract: Background Chlamydial infection is a difficult-to-diagnose type of sexually transmitted disease that occurs mainly in young people. We report a case of bowel obstruction caused by intrapelvic adhesions formed by chlamydial infection. Case presentation This patient was a 23-year-old woman who had been suffering from acute abdominal pain. She had been previously treated several times for intrapelvic abscesses and had a history of chlamydial infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…This study found the incidence of intestinal obstruction in 1,211 patients with shigellosis to be 2.5% [ 1 ]. Various case reports have described intestinal obstruction caused by parasites [ 5 - 12 ], Chlamydia trachomatis [ 13 - 15 ], intrauterine device infection [ 16 ], mpox [ 17 ], and Mycobacterium avium complex infection [ 18 ]. To our knowledge, this is the first case report of prolonged ileus caused by shigellosis after bilateral open inguinal hernia repair and open umbilical hernia repair in an adult.…”
Section: Discussionmentioning
confidence: 99%
“…This study found the incidence of intestinal obstruction in 1,211 patients with shigellosis to be 2.5% [ 1 ]. Various case reports have described intestinal obstruction caused by parasites [ 5 - 12 ], Chlamydia trachomatis [ 13 - 15 ], intrauterine device infection [ 16 ], mpox [ 17 ], and Mycobacterium avium complex infection [ 18 ]. To our knowledge, this is the first case report of prolonged ileus caused by shigellosis after bilateral open inguinal hernia repair and open umbilical hernia repair in an adult.…”
Section: Discussionmentioning
confidence: 99%